Overlapping Features in Kawasaki Disease-Related Arthritis and Systemic-Onset Juvenile Idiopathic Arthritis: A Nationwide Study in Japan - Kanemasa, Hikaru; Nanishi, Etsuro; Takada, Hidetoshi; Ishimura, Masataka; Nishio, Hisanori; Honjo, Satoshi; Masuda, Hiroshi; Nagai, Noriko; Nishihara, Takahiro; Ishii, Tohru; Adachi, Takenori; Hara, Satoshi; et al. (Frontiers in Pediatrics, 2021)
Background: Arthritis occurs after the diagnosis of Kawasaki disease (KD). Most cases are self-limiting; however, some patients require prolonged treatment. Method: To characterize KD-related arthritis, 14 patients who required arthritis treatment within 30 days after the diagnosis of KD were recruited from the 23rd KD survey in Japan. Twenty-six additional patients were included in our tertiary center and literature review to differentiate KD-related arthritis from systemic-onset juvenile idiopathic arthritis (SoJIA). Results: The estimated prevalence of KD-related arthritis in Japan was 48 per 100,000 KD patients. Patients with KD-related arthritis had an older age at onset (P=0.002) and higher rate of intravenous immunoglobulin (IVIG) resistance (P<0.001, 86%) in comparison to those without arthritis. Among 40 patients, 18 had arthritis in the acute phase KD (continued fever-onset type) and 22 did in the convalescent phase (interval fever-onset type). Both showed a similar rate of complete KD or IVIG response. Interval-type patients required biologics for arthritis control less frequently (5% vs. 39%, P=0.02) and had a higher 2-year off-treatment rate (100% vs. 43%, P=0.009) than continued-type ones. Interval-types showed lower serum ferritin and interleukin-18 levels than continued-types. When continued-types were grouped according to whether or not they required biologics (n=7 and n=11, respectively), the former subgroup had higher ferritin and interleukin-18 levels (P=0.01, 0.02). A canonical discriminant analysis differentiated interval-type from continued-type with the combination of age, time to arthritis, and the ferritin and matrix metalloproteinase-3 levels. Conclusion: Arthritis requiring treatment is a rare complication of KD. KD-associated arthritis includes interval-type (KD-reactive) and continued-type (true SoJIA requiring biologics), and overlapping arthritis, suggesting the pathophysiological continuity of autoinflammation between KD and JIA.